An Industry Equilibrium Analysis of Downstream Vertical Integration - McGuire, Timothy W; Staelin, Richard (Marketing science (Providence, R.I.), 2008)
This paper investigates the effect of product substitutability on Nash equilibrium distribution structures in a duopoly where each manufacturer distributes its goods through a single exclusive retailer, which may be either a franchised outlet or a factory store. Static linear demand and cost functions are assumed, and a number of rules about players' expectations of competitors' behavior are examined. It is found that for most specifications product substitutability does influence the equilibrium distribution structure. For low degrees of substitutability, each manufacturer will distribute its product through a company store; for more highly competitive goods, manufacturers will be more likely to use a decentralized distribution system. This article was originally published in Marketing Science , Volume 2, Issue 2, pages 161–191, in 1983.